Pattern and Determinant of Contraceptive Use among Women in Indonesia from 2007 to 2017: Evidence from Demographic and Health Survey - Fajarningtiyas, Desy Nuri; Sulistiawan, Dedik; Naibaho, Margareth Maya Parulianta; Arifa, Riza Fatma (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Modern contraceptives are proven as the most effective birth control methods. However, it was a change in the pattern of modern method use in Indonesia to traditional. Objectives: This study investigated the pattern of contraceptive use and its determinant in Indonesia between 2007 and 2017. Methods: The study employed data from the Indonesian Demographic and Health Survey (IDHS) 2007, 2012, and 2017. Eligible participants included all women aged 15–49 who were married/living together with a partner. The dependent variable was contraceptive method use categorized as long-term, short-term, and traditional. Weighted pooled logistic regression analysis was applied to determine the shifting patterns of the independent variables related to contraceptive use over time. Results: The trend of contraceptive use in Indonesia has shifted over the three periods of the IDHS. During the three survey periods, contraceptive use was still dominated by short-term contraception, although over the last five years, the proportion has shown a decline of around 9%. Traditional contraceptive adoption followed the same patterns as long-acting reversible contraception (LARC), although having a smaller prevalence. Education level was significantly unassociated with the use of the traditional method at the beginning of the observation. However, more educated and knowledgeable women about contraceptive methods were more likely to use traditional contraceptives, switched from long-acting use following the next five and ten years. Long-term methods were no longer significantly more common among women in Java and Bali after five and ten years; the likelihood of using traditional methods in Java and Bali was growing. Conclusion: This study showed that contraceptive use and determinants were always dynamic over time. Therefore, family planning strategies and policies should adapt accordingly. Giving an understanding of contraceptive methods’ benefits and risks through adequate method information is encouraged to prevent contraceptive dropout or switch to less-effective methods.